Method for improving erosion resistance of pottery pipe runner pipe

By applying lateral vibration during the extrusion process of the ceramic pipe and performing high aluminum content coating on the inner wall of the ceramic pipe, the adhesion problem caused by excessive porosity of the ceramic pipe is solved, the corrosion resistance of the ceramic pipe is improved, and the special The demand for steel casting process.

CN119462184APending Publication Date: 2025-02-18BAOJI HUAGUANG CASTING MATERIAL TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411693702.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

During the casting process of special steel, existing ceramic pipes have serious adhesion problems due to high porosity, and insufficient corrosion resistance, making it difficult to meet the requirements of high temperature and high corrosion.

Method used

By applying lateral vibration during the extrusion process, the inner wall of the ceramic tube is compacted and the inner wall of the ceramic tube is coated after firing, the coating is prepared using inorganic aggregate with high aluminum content and water-soluble inorganic binder. Bake the fixed coating at 550~650℃.

Benefits of technology

It reduces the porosity of the inner wall of the ceramic pipe, improves the corrosion resistance of the ceramic pipe, significantly reduces the adhesion problem, and meets the needs of special steel casting processes.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a method for improving erosion resistance of a pottery pipe pouring gate pipe, which comprises the following steps of: preparing high-alumina clinker and combined clay, preparing mud, pugging and aging to obtain a mud material for extruding the pipe; the method comprises the following steps: extruding a pipe by adopting pug, and compacting the inner wall of the extruded pug pipe by applying transverse vibration during pipe extrusion, so as to obtain the pug pipe with the compacted inner wall; shaping and drying the mud pipe with the densified inner wall, and then firing to obtain a ceramic pipe finished product with the densified inner wall; preparing a batch for the coating; coating the inner wall of the ceramic tube finished product with the densified inner wall by using the batch for coating to obtain the ceramic tube finished product with the coated inner wall; and naturally drying the ceramic tube finished product of which the inner wall is coated, and then baking to obtain the ceramic pouring gate tube with high erosion resistance. According to the process technical method, the requirement of a special steel casting process can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of refractory materials for metal casting, and in particular relates to a method for improving the anti-corrosion performance of a ceramic pipe pouring pipe. Background Art

[0002] In the process of steel smelting and casting, a refractory runner tube is often used for pouring. This runner tube is usually called a ceramic runner tube or a ceramic tube. The main function of the ceramic tube for casting is to separate the sand mold from the molten metal to prevent the molten metal from washing the coating and sand on the inner wall of the cavity runner, causing slag inclusion defects in the casting. Existing ceramic tubes are generally made of high-alumina clinker and combined with clay. The preparation process generally uses the following process: crushing the raw clinker → screening and grading → batching according to the formula and particle grading → mixing to make plastic mud → kneading → aging → plastic method extrusion tube molding → drying → firing.

[0003] Ceramic runner tubes can be divided into several types according to their use occasions in the process of pouring molten steel, including ordinary cast iron, ductile iron, ordinary cast steel and special cast steel. Ceramic tubes for different purposes can be made according to the adjustment of the ingredient formula and the preparation process. The main problems of ceramic tubes in actual use have always been: adhesion, delamination, cracking, low refractoriness, etc. Generally speaking, the pouring temperature of cast iron is low and the corrosiveness is not too strong, so the requirements for the ingredient formula and preparation process of ceramic tubes for cast iron are not high, and it is relatively easy to prepare products that meet the requirements. Although the pouring temperature of ordinary cast steel is higher and the corrosiveness of molten steel is stronger, after years of hard work, we have basically solved the problems of adhesion, delamination, cracking, low refractoriness, etc. by optimizing the ingredient formula and preparation process, and increasing the firing temperature.

[0004] However, for special steels, such as high chromium steel, high manganese steel, high molybdenum steel, etc., due to the high pouring temperature of special steel and the strong corrosiveness of molten steel, very high requirements are placed on the performance of ceramic tubes, which cannot be met by general ceramic tubes. Over the years, various measures have been taken to optimize the batching formula, improve the particle grading, and increase the mullite phase content in ceramic tubes, and special ceramic tubes for casting have been prepared, which basically solves the problems of cracking, low refractoriness, and low strength, but it is still not good enough to solve the adhesion problem during the use of ceramic tubes.

[0005] The root cause of the adhesion problem is that the apparent porosity of the inner wall of the ceramic tube is too high. The apparent porosity is a very important performance indicator of ceramic tubes. When the apparent porosity is too high, for example, more than 25%, due to the high temperature of the special steel casting molten steel and strong corrosiveness, the molten steel will easily penetrate into the apparent pores of the ceramic tube and adhere to the inner wall of the ceramic tube. But when the apparent porosity is too low, for example, less than 20%, it often reduces the thermal shock resistance of the ceramic tube. Therefore, it must be grasped well. The optimal range of apparent porosity is 21~23%. The apparent porosity of our ceramic tubes is above 25%. Obviously, the weak corrosion resistance is the biggest weakness. Summary of the invention

[0006] The purpose of the present invention is to provide a method for improving the erosion resistance of a ceramic pipe runner tube to overcome the problem of high apparent porosity in the above-mentioned prior art. According to the process technology method of the present invention, the needs of special steel casting technology can be met.

[0007] The present invention is achieved through the following technical solutions: A method for improving the erosion resistance of a ceramic pipe runner pipe comprises the following steps: Step 1: Take high-alumina clinker and combined clay for batching, mud making, mud kneading and aging to obtain mud for pipe extrusion; Step 2: Extruding a tube using the clay obtained in step 1, and applying lateral vibration during the extrusion to densify the inner wall of the extruded clay tube to obtain a clay tube with a densified inner wall; Step 3: shaping and drying the clay tube with a compacted inner wall, and then firing it to obtain a finished ceramic tube with a compacted inner wall; Step 4: preparing a coating material; Step 5: coating the inner wall of the finished ceramic tube with densified inner wall by using a coating compound to obtain a finished ceramic tube with inner wall coating; Step 6: The finished ceramic tube with the inner wall coating is naturally dried and then baked to obtain a ceramic runner tube with high corrosion resistance.

[0008] Furthermore, the high-alumina clinker in step 1 is a combination of high-alumina stone, coke stone and light-burned bauxite, and the weight percentage is 2-3 parts of high-alumina stone, 2-3 parts of coke stone and 4-6 parts of light-burned bauxite; The combined clay is a combination of clay, illite and bentonite, and the weight percentage is 3-4 parts of clay, 3-4 parts of illite and 2-4 parts of bentonite; When the high-alumina clinker and the binding clay are mixed, the high-alumina clinker is 68-72% and the binding clay is 28-32% by mass fraction.

[0009] Furthermore, during the tube extrusion in step 2, a vibration device is installed on the inner core of the tube extruder so that the inner core can generate lateral vibrations at a frequency of 300 times / minute.

[0010] Furthermore, in step 2, the sintering temperature is 1250-1300° C. and the sintering time is 3-5 hours.

[0011] Furthermore, the raw materials for preparing the coating batch include inorganic aggregate, coating liquid suspension agent and binder; Among them, high-alumina raw materials are used, crushed through a 300-mesh sieve, as inorganic aggregates; clay is used, crushed through a 300-mesh sieve, as a coating liquid suspension agent; water-soluble inorganic binder powder is used as a binder; The high-alumina raw material includes mullite powder and alumina powder, the clay is bentonite, montmorillonite, kaolin or attapulgite clay, and the water-soluble inorganic binder powder is silica sol or water glass with a modulus M of 2.2-2.5.

[0012] Furthermore, the preparation process of the coating batch is specifically as follows: mullite powder and alumina powder are mixed in a mass ratio of (1-0.5): (0-0.5) to obtain an inorganic aggregate mixture; clay is added in a ratio of 2%-10% of the mass of the inorganic aggregate mixture, and then a water-soluble inorganic binder powder is added in a ratio of 10%-18% of the mass of the inorganic aggregate mixture, and the mixture is fully stirred and mixed to obtain the coating batch.

[0013] Furthermore, step five is specifically as follows: adding water to the coating batch, the amount of water added is 50% to 90% of the mass of the coating batch, to obtain a coating slurry, placing the finished ceramic tube with inner wall densification upright, filling its inner cavity with the coating slurry, letting it stand for 5 to 30 seconds, then inverting the finished ceramic tube with inner wall densification, letting it stand for another 5 to 30 seconds, and then discharging the remaining coating slurry to obtain a finished ceramic tube with inner wall coating.

[0014] Furthermore, the coating thickness of the ceramic tube finished product with the inner wall coating is 0.2-0.8 mm.

[0015] Furthermore, in step six, the baking temperature is 550-650° C. and the baking time is 30 minutes.

[0016] A ceramic pipe pouring channel pipe is obtained by adopting the method for improving the anti-corrosion performance of a ceramic pipe pouring channel pipe, wherein the apparent porosity of the inner wall of the ceramic pipe pouring channel pipe is 21.1-22.6%.

[0017] Compared with the prior art, the present invention has the following beneficial technical effects: Firstly, the present invention generates lateral vibration during the extrusion process of the clay tube, and the inner wall of the clay tube is densified by vibration, so that the apparent porosity of the inner wall of the ceramic tube is preliminarily reduced. Secondly, the inner wall of the finished ceramic tube with the inner wall densified and fired at high temperature is coated, and the obtained ceramic runner tube has strong corrosion resistance and can meet the needs of special steel casting process.

[0018] The coating used in the present invention has three major characteristics: first, the raw material constituting the coating is an inorganic raw material with a high aluminum content, which is similar to the raw material performance of the ceramic tube itself; and the coating is baked at 550-650° C., thereby ensuring that the coating is firmly bonded to the substrate and will not peel off due to the scouring of molten steel pouring; second, the coating raw material has a fine particle size, and the pores formed after the coating is dried are small and uniform, which can ensure that the apparent porosity of the inner wall of the ceramic tube is in the range of 21-23%; third, due to the isolation of the coating, the molten steel in the casting process will not directly contact the inner wall of the ceramic tube, so there will be no adhesion and peeling caused by erosion of the molten steel. DETAILED DESCRIPTION

[0019] The present invention is described in detail below: A method for improving the erosion resistance of a ceramic pipe runner pipe comprises the following steps: Step 1, selecting high-alumina clinker (a combination of high-alumina stone, pyroxene stone, and bauxite light-burned material, calculated by weight, 2-3 parts of high-alumina stone, 2-3 parts of pyroxene stone, and 4-6 parts of bauxite light-burned material) and binding clay (a combination of clay, illite, and bentonite, calculated by weight, 3-4 parts of clay, 3-4 parts of illite, and 2-4 parts of bentonite), and batching, mud making, mud training, and aging according to a formula of 68-72% of high-alumina clinker and 28-32% of binding clay; Step 2: Install a vibration device on the inner core of the tube extruder so that the inner core can generate lateral vibrations at a frequency of 300 times per minute. The lateral vibration of the inner core of the tube extruder during tube extrusion can densify the inner wall of the extruded mud tube; Step three, shaping and drying the extruded clay tube with a densified inner wall, and then firing it to obtain a finished ceramic tube with a densified inner wall, the firing temperature is 1250-1300° C., and the time is 3-5 hours.

[0020] Step 4, prepare the coating material, select high-alumina raw materials (mullite powder and alumina powder), crush them through a 300-mesh sieve, as the inorganic aggregate in the coating; select high-quality clay (such as bentonite, montmorillonite, kaolin, attapulgite clay), crush them through a 300-mesh sieve, as the coating liquid suspension agent; select water-soluble inorganic binder powder (such as water glass with a modulus M=2.2~2.5, silica sol, etc.) as the binder of the inorganic aggregate.

[0021] First, high-alumina raw materials mullite powder and alumina powder are mixed in a mass ratio of mullite / alumina = (1~0.5) / (0~0.5) to obtain an inorganic aggregate mixture; then high-quality clay is added in a ratio of 2%~10% of the mass of the inorganic aggregate mixture to obtain a secondary mixture; then water-soluble inorganic binder powder is added in a ratio of 10%~18% of the mass of the inorganic aggregate mixture, and the mixture is fully stirred and mixed to obtain a coating batch.

[0022] Step 5: coating the inner wall of the finished ceramic tube. Add water as a dispersing medium to the coating batch. The amount of water added is related to the coating method. The coating methods include: grouting coating, spraying, rolling, brushing, dipping, etc., and the present invention preferably uses grouting coating. According to the grouting coating, the amount of water added is 50% to 90% of the mass of the coating batch to obtain coating slurries of different concentrations.

[0023] Key points of grouting coating method: Place the finished ceramic tube upright, fill its inner cavity with coating slurry, let it stand for 5 to 30 seconds, then turn the finished ceramic tube upside down, let it stand for another 5 to 30 seconds, and then discharge the remaining slurry to form a 0.2 to 0.8 mm thick coating on the inner wall of the finished ceramic tube.

[0024] Step six, after the finished ceramic tube with inner wall coating is naturally dried, it is baked in a dryer at 550-650° C. for about 30 minutes to obtain a ceramic runner tube with high corrosion resistance. The inner wall apparent porosity of the obtained ceramic runner tube is 21.1-22.6%.

[0025] The embodiments of the present invention will be described in detail below in conjunction with the examples. The implementation cases are preferred embodiments of the present invention and should not be used to limit the scope of the present invention. In the following examples, the methods and experimental equipment used are all conventional methods and instruments unless otherwise specified.

[0026] Example 1 1. Select high-alumina clinker (a combination of 2 parts of high-alumina stone, 3 parts of coke stone, and 5 parts of light-burned bauxite) and combined clay (a combination of 3 parts of clay, 4 parts of illite, and 3 parts of bentonite), and mix, make mud, knead mud, and age according to the ratio of 68% of high-alumina clinker and 32% of combined clay to obtain mud for pipe extrusion; 2. The inner core of the tube extruder generates lateral vibration at a frequency of 300 times / minute to extrude the tube, so that the inner wall of the extruded mud tube is densified; 3. The clay tube with a compacted inner wall is shaped and dried, and then fired at a temperature of 1250° C. for 5 hours to obtain a finished ceramic tube with a compacted inner wall.

[0027] 4. Prepare the coating batch. Select mullite powder and alumina powder, crushed through a 300-mesh sieve respectively, as the inorganic aggregate in the coating; select bentonite, crushed through a 300-mesh sieve, as the coating liquid suspension; select water glass with a modulus M of 2.2 as the binder of the inorganic aggregate.

[0028] First, mullite powder and alumina powder are mixed in a mass ratio of mullite / alumina = 0.5 / 0.5 to obtain an inorganic aggregate mixture; then bentonite is added in a ratio of 10% of the mass of the inorganic aggregate mixture to obtain a secondary mixture; then water glass is added in a ratio of 18% of the mass of the inorganic aggregate mixture, and the mixture is fully stirred and mixed to obtain a coating batch.

[0029] 5. Coating the inner wall of the finished ceramic tube. Use the grouting method. Add water to the coating batch according to 90% of the batch mass to prepare the coating slurry. Place the finished ceramic tube upright, fill its inner cavity with the coating slurry, let it stand for 30 seconds, then turn the finished ceramic tube upside down, let it stand for another 30 seconds, and then discharge the remaining slurry to form a 0.5mm thick coating on the inner wall of the finished ceramic tube.

[0030] 6. After the finished ceramic tube with inner wall coating is naturally dried, it is baked in a dryer at 550°C for about 30 minutes to obtain a ceramic runner tube with high corrosion resistance.

[0031] The apparent porosity of the inner wall of the obtained ceramic pipe pouring channel tube is 21.6%.

[0032] Example 2 1. Select high-alumina clinker (a combination of 3 parts of high-alumina stone, 2 parts of coke stone, and 5 parts of light-burned bauxite) and combined clay (a combination of 4 parts of clay, 3 parts of illite, and 3 parts of bentonite), and mix, make mud, knead mud, and age according to the ratio of 72% of high-alumina clinker and 28% of combined clay to obtain mud for pipe extrusion; 2. The inner core of the tube extruder generates lateral vibration at a frequency of 300 times / minute to extrude the tube, so that the inner wall of the extruded mud tube is densified; 3. The clay tube with a densified inner wall is shaped and dried, and then fired at a temperature of 1300° C. for 3 hours to obtain a finished ceramic tube with a densified inner wall.

[0033] 4. Prepare the coating batch. Select mullite powder and alumina powder, crushed through a 300-mesh sieve respectively, as the inorganic aggregate in the coating; select montmorillonite, crushed through a 300-mesh sieve, as the coating liquid suspension; select water glass with a modulus M of 2.5 as the binder of the inorganic aggregate.

[0034] First, mullite powder and alumina powder are mixed in a ratio of mullite / alumina = 0.6 / 0.4 to obtain an inorganic aggregate mixture; then, montmorillonite powder is added in a ratio of 2% of the mass of the inorganic aggregate mixture to obtain a secondary mixture; then, water glass is added in a ratio of 10% of the mass of the inorganic aggregate mixture, and the mixture is fully stirred to obtain a coating batch.

[0035] 5. Coating the inner wall of the finished ceramic tube. Use the grouting method. Add water to the coating batch according to 80% of the batch weight to prepare the coating slurry. Place the finished ceramic tube upright, fill its inner cavity with the coating slurry, let it stand for 25 seconds, then turn the finished ceramic tube upside down, let it stand for another 25 seconds, and then discharge the remaining slurry to form a 0.6mm thick coating on the inner wall of the finished ceramic tube.

[0036] 6. After the finished ceramic tube with inner wall coating is naturally dried, it is baked in a dryer at 650°C for about 30 minutes to obtain a ceramic runner tube with high corrosion resistance.

[0037] The apparent porosity of the inner wall of the obtained ceramic pipe pouring channel tube is 22.0%.

[0038] Example 3 1. Select high-alumina clinker (a combination of 3 parts of high-alumina stone, 3 parts of coke stone, and 4 parts of bauxite light-burned material) and combined clay (a combination of 3 parts of clay, 3 parts of illite, and 4 parts of bentonite), and mix, make mud, knead mud, and age according to the ratio of 70% of high-alumina clinker and 30% of combined clay to obtain mud for pipe extrusion; 2. The inner core of the tube extruder generates lateral vibration at a frequency of 300 times / minute to extrude the tube, so that the inner wall of the extruded mud tube is densified; 3. The clay tube with a compacted inner wall is shaped and dried, and then fired at a temperature of 1280° C. for 4 hours to obtain a finished ceramic tube with a compacted inner wall.

[0039] 4. Prepare the coating batch. Select mullite powder and alumina powder, crushed through a 300-mesh sieve respectively, as the inorganic aggregate in the coating; select kaolin, crushed through a 300-mesh sieve, as the coating liquid suspension; select water glass with a modulus M of 2.3 as the binder of the inorganic aggregate.

[0040] First, mullite powder and alumina powder are mixed in a ratio of mullite / alumina = 0.8 / 0.2 to obtain an inorganic aggregate mixture; then, kaolin is added in a ratio of 5% of the mass of the inorganic aggregate mixture to obtain a secondary mixture; then, water glass is added in a ratio of 16% of the mass of the inorganic aggregate mixture, and the mixture is fully stirred to obtain a coating batch.

[0041] 5. Coating the inner wall of the finished ceramic tube. Use the grouting method. Add water to the coating batch according to 70% of the batch weight to prepare the coating slurry. Place the finished ceramic tube upright, fill its inner cavity with the coating slurry, let it stand for 20 seconds, then turn the finished ceramic tube upside down, let it stand for another 20 seconds, and then discharge the remaining slurry to form a 0.8mm thick coating on the inner wall of the finished ceramic tube.

[0042] 6. After the finished ceramic tube with inner wall coating is naturally dried, it is baked in a dryer at 600°C for about 30 minutes to obtain a ceramic runner tube with high corrosion resistance.

[0043] The apparent porosity of the inner wall of the obtained ceramic pipe pouring channel tube is 22.6%.

[0044] Example 4 1. Select high-alumina clinker (a combination of 2 parts of high-alumina stone, 2 parts of coke stone, and 6 parts of light-burned bauxite) and combined clay (a combination of 4 parts of clay, 4 parts of illite, and 2 parts of bentonite), and mix, make mud, knead mud, and age according to the ratio of 69% of high-alumina clinker and 31% of combined clay to obtain mud for pipe extrusion; 2. The inner core of the tube extruder generates lateral vibration at a frequency of 300 times / minute to extrude the tube, so that the inner wall of the extruded mud tube is densified; 3. The clay tube with a compacted inner wall is shaped and dried, and then fired at a temperature of 1280° C. for 4 hours to obtain a finished ceramic tube with a compacted inner wall.

[0045] 4. Prepare the coating batch. Select mullite powder and alumina powder, crushed through a 300-mesh sieve respectively, as the inorganic aggregate in the coating; select attapulgite clay, crushed through a 300-mesh sieve, as the coating liquid suspension; select water glass with a modulus M of 2.2 as the binder of the inorganic aggregate.

[0046] First, mullite powder and alumina powder are mixed in a ratio of mullite / alumina = 0.8 / 0.2 to obtain an inorganic aggregate mixture; then, attapulgite clay is added in a ratio of 8% of the mass of the inorganic aggregate mixture to obtain a secondary mixture; then, water glass is added in a ratio of 14% of the mass of the inorganic aggregate mixture, and the mixture is fully stirred to obtain a coating batch.

[0047] 5. Coating the inner wall of the finished ceramic tube. Use the grouting method. Add water to the coating batch according to 60% of the batch weight to prepare the coating slurry. Place the finished ceramic tube upright, fill its inner cavity with the coating slurry, let it stand for 15 seconds, then turn the finished ceramic tube upside down, let it stand for another 15 seconds, and then discharge the remaining slurry to form a 0.4mm thick coating on the inner wall of the finished ceramic tube.

[0048] 6. After the finished ceramic tube with inner wall coating is naturally dried, it is baked in a dryer at 580°C for about 30 minutes to obtain a ceramic runner tube with high corrosion resistance.

[0049] The apparent porosity of the inner wall of the obtained ceramic pipe pouring channel tube is 21.1%.

[0050] Example 5 1. Select high-alumina clinker (a combination of 2 parts of high-alumina stone, 2 parts of coke stone, and 6 parts of light-burned bauxite) and combined clay (a combination of 3 parts of clay, 4 parts of illite, and 3 parts of bentonite), and mix, make mud, knead mud, and age according to the ratio of 71% of high-alumina clinker and 29% of combined clay to obtain mud for pipe extrusion; 2. The inner core of the tube extruder generates lateral vibration at a frequency of 300 times / minute to extrude the tube, so that the inner wall of the extruded mud tube is densified; 3. The clay tube with a compacted inner wall is shaped and dried, and then fired at a temperature of 1250° C. for 5 hours to obtain a finished ceramic tube with a compacted inner wall.

[0051] 4. Prepare the coating materials. Select mullite powder, crushed through a 300-mesh sieve, as the inorganic aggregate in the coating; select bentonite, crushed through a 300-mesh sieve, as the coating liquid suspension; select silica sol (tetraethyl orthosilicate) as the binder of the inorganic aggregate.

[0052] First, the mullite powder is mixed in the ratio of mullite / alumina = 1.0 / 0, that is, all the mullite powder is used as the inorganic aggregate; then bentonite is added at a ratio of 2% of the mass of the inorganic aggregate to obtain a secondary mixture: then tetraethyl orthosilicate is added at a ratio of 12% of the mass of the inorganic aggregate, and the mixture is fully stirred to obtain a coating compound.

[0053] 5. Coating the inner wall of the finished ceramic tube. Use the grouting method. Add water to the coating batch according to 50% of the batch weight to prepare the coating slurry. Place the finished ceramic tube upright, fill its inner cavity with the coating slurry, let it stand for 5 seconds, then turn the finished ceramic tube upside down, let it stand for another 5 seconds, and then discharge the remaining slurry to form a 0.2mm thick coating on the inner wall of the finished ceramic tube.

[0054] 6. After the finished ceramic tube with inner wall coating is naturally dried, it is baked in a dryer at 630°C for about 30 minutes to obtain a ceramic runner tube with high corrosion resistance.

[0055] The apparent porosity of the inner wall of the obtained ceramic pipe pouring channel tube is 21.8%.

[0056] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.

Claims

1. A method for improving the corrosion resistance of a ceramic pipe runner pipe, characterized in that: The following steps are involved: Step 1: Take high-alumina clinker and combined clay for batching, mud making, mud training and aging to obtain mud for pipe extrusion; Step 2: Extruding a tube using the clay obtained in step 1, and applying lateral vibration during the extrusion to densify the inner wall of the extruded clay tube to obtain a clay tube with a densified inner wall; Step 3: shaping and drying the clay tube with a compacted inner wall, and then firing it to obtain a finished ceramic tube with a compacted inner wall; Step 4: preparing a coating material; Step 5: coating the inner wall of the finished ceramic tube with densified inner wall by using a coating batch material to obtain a finished ceramic tube with inner wall coating; Step 6: The finished ceramic tube with the inner wall coating is naturally dried and then baked to obtain a ceramic runner tube with high corrosion resistance.

2. A method for improving the corrosion resistance of a ceramic pipe runner pipe according to claim 1, characterized in that: The high-alumina clinker in step 1 is a combination of high-alumina stone, coke stone and bauxite light-burned material, and the weight percentage is 2-3 parts of high-alumina stone, 2-3 parts of coke stone and 4-6 parts of bauxite light-burned material; The combined clay is a combination of clay, illite and bentonite, and the weight percentage is 3-4 parts of clay, 3-4 parts of illite and 2-4 parts of bentonite; When the high-alumina clinker and the binding clay are mixed, the high-alumina clinker is 68-72% and the binding clay is 28-32% by mass fraction.

3. A method for improving the corrosion resistance of a ceramic pipe runner pipe according to claim 1, characterized in that: During the tube extrusion in step 2, a vibration device is installed on the inner core of the tube extruder so that the inner core can generate lateral vibrations at a frequency of 300 times / minute.

4. A method for improving the corrosion resistance of a ceramic pipe runner pipe according to claim 1, characterized in that: The sintering temperature in step 2 is 1250-1300°C and the sintering time is 3-5 hours.

5. The method for improving the corrosion resistance of a ceramic pipe runner pipe according to claim 1, characterized in that: The raw materials for preparing the coating batch include inorganic aggregate, coating liquid suspension agent and binder; Among them, high-alumina raw materials are used, crushed through a 300-mesh sieve, as inorganic aggregates; clay is used, crushed through a 300-mesh sieve, as a coating liquid suspension agent; water-soluble inorganic binder powder is used as a binder; The high-alumina raw material includes mullite powder and alumina powder, the clay is bentonite, montmorillonite, kaolin or attapulgite clay, and the water-soluble inorganic binder powder is silica sol or water glass with a modulus M of 2.2-2.

5.

6. A method for improving the corrosion resistance of a ceramic pipe runner pipe according to claim 5, characterized in that: The preparation process of the coating batch is specifically as follows: mullite powder and alumina powder are mixed in a mass ratio of (1-0.5): (0-0.5) to obtain an inorganic aggregate mixture; clay is added in a ratio of 2%-10% of the mass of the inorganic aggregate mixture, and then a water-soluble inorganic binder powder is added in a ratio of 10%-18% of the mass of the inorganic aggregate mixture, and the mixture is fully stirred and mixed to obtain the coating batch.

7. A method for improving the corrosion resistance of a ceramic pipe runner pipe according to claim 1, characterized in that: Step five is specifically as follows: adding water to the coating batch material, the amount of water added is 50% to 90% of the mass of the coating batch material, obtaining a coating slurry, placing the finished ceramic tube with inner wall densification upright, filling its inner cavity with the coating slurry, standing for 5 to 30 seconds, then inverting the finished ceramic tube with inner wall densification, and standing for another 5 to 30 seconds, and then discharging the remaining coating slurry to obtain a finished ceramic tube with inner wall coating.

8. A method for improving the corrosion resistance of a ceramic pipe runner pipe according to claim 7, characterized in that: The coating thickness of the ceramic tube finished product of the inner wall coating is 0.2-0.8 mm.

9. The method for improving the corrosion resistance of a ceramic pipe runner pipe according to claim 1, characterized in that: The baking temperature in step six is ​​550-650°C and the baking time is 30 minutes.

10. A ceramic pipe pouring pipe, characterized in that: The method for improving the erosion resistance of a ceramic pipe runner tube according to any one of claims 1 to 9 is adopted, wherein the apparent porosity of the inner wall of the ceramic pipe runner tube is 21.1-22.6%.

Citation Information

Patent Citations

  • Glaze-crawling-proof protection coating for immersion type water gap slag line and preparation method of glaze-crawling-proof protection coating

    CN105693289A

  • Multi-layer composite runner brick and production method thereof

    CN106187248A

  • Durable paper runner tube used for casting and making method thereof

    CN106588047A

  • Special runner pipe for casting and preparation method thereof

    CN107311674A

  • Ceramic aggregate for mold and method for producing the same, and mold using the same

    JP2009220143A